Citizen Socio-Economic Changes in Sukamulya Village After The Establishment of West Java International Airport - Hermawan, Asterina (International Journal Pedagogy of Social Studies, 2021)
West Java International Airport (BIJB) is a Regionally-Owned Enterprises (BUMD) which was established by West Java Provincial Government. West Java International Airport is located in Kertajati Majalengka. This study aims to know citizen of Sukamulya socioeconomic changes after the establishment of West Java International Airport. This study used the case study method of qualitative approach, the data was collected through observation, interview, and documentation of the citizen of Sukamulya Village. The result shows: 1) There is shifting in citizen’s livelihood, from agrarian to nonagrarian. (2) there has been no enchancement equalization in citizen income. (3) After the establishment of BIJB, citizen upgrade land ownership status to become certification to increase the selling value of the land.